Abdulla Avloni's Way of Life - Rahimjonova Dilfuza (Peerian Journals Publishing, 2023)
Abdulla Avloni is a great poet, writer, playwright, pedagogue, journalist and public figure, one of the founders of Uzbek culture and literature. He brought Uzbek pedagogy, dramaturgy, national theater, journalism, and children's literature to a new level. It is no exaggeration to say that Abdulla Avloni, a mature scientist and pedagogue, introduced a number of changes and updates to the field of education and science and the teaching process through his innovative actions and pedagogical views. Based on his pedagogical views, he finds a solution to the issues of interactivity, activity, mutual respect and education among students of schools and higher education institutions. In several pedagogical works written by Abdulla Avloni, he pays serious attention to the principles of upbringing and ethics and the field of education. In this article, we will study the pedagogical views of Abdulla Avloni and the issue of education in his works.
Keywords: Abdulla Avloni; Uzbek pedagogy; pedagogical activity